Polycythemia vera: Correlation of JAK2V617F mutation with clinicohematologic characteristics. A single centre experience. - Deepti Mutreja; Sudha Sazawal; Sunita Chhikara; Manoranjan Mahapatra; Pravas Mishra; Tulika Seth; Renu Saxena (Mediterranean Journal of Hematology and Infectious Diseases, 2014)
Introduction